Peer Supporters of Yayasan Sebaya Lancang Kuning Supporting Antiretroviral Therapy Adherence Among People Living With HIV In Padang City 2026 - Azzahra, Hasya Tsania; Markolinda, Yessy; Triana, Vivi (Jurnal Kesmas Jambi, 2026)
Antiretroviral therapy (ART) adherence remains a critical gap in HIV care, with Indonesia falling short of the 95-95-95 targets and a 26% loss-to-follow-up rate. Community-based peer support is recommended to improve adherence, yet most studies emphasize quantifiable outcomes rather than the subjective experiences involved. This study explored the role of Peer Supporters from Yayasan Sebaya Lancang Kuning in supporting ART adherence among people living with HIV (PLHIV) in Padang City in 2026, across four social support dimensions: emotional, appraisal, instrumental, and informational. A qualitative phenomenological design was employed. Data were collected through in-depth interviews with nine purposively selected informants (four peer supporters, one program coordinator, and four PLHIV clients), supplemented by non-participatory observation and document review, and analyzed using the Miles and Huberman interactive model with source and method triangulation. Emotional support — built through confidentiality assurance, non-judgmental attitudes, and supporters' self-disclosure as fellow PLHIV — served as the foundation enabling other forms of support. Appraisal support was delivered through motivation, recognition of achievements, and supporters acting as role models. Instrumental support encompassed healthcare navigation, administrative assistance, medication delivery, and advocacy against discrimination, despite persisting stigma and client dependency. Informational support was provided progressively, from service access guidance to correcting health misinformation using concrete evidence. Peer supporters also reported substantial emotional burden. Peer support plays a multidimensional role in sustaining ART adherence, though sustainability requires attention to supporters' psychological wellbeing, clearer assistance guidelines, and stronger capacity to counter misinformation.